Desarrollo de una aplicación web progresiva para la gestión de servicios en la Corporación Pioneer de la ciudad de Latacunga, mediante el uso de prácticas ágiles - Lisintuña Candelejo, Brayan Dario (2022)
The present work is based on a technological proposal that was carried out in the Pioneer Corporation of the city of Latacunga, about the management of services through the use of agile practices, the same that is currently carried out manually and with means that are not adequate for their respective storage, causing loss of time, there is no order in each activity, it should be emphasized that in the development of the theoretical framework, books, theses, scientific articles were investigated, to have ample and reliable information, where the main objective was to analyze, know, interpret and observe the procedure applied in each process. Through a dialogue with the Manager Mr. Milton Cando, needs were gathered through an interview, who provided the essential requirements to proceed with the development, design and programming of the project with the intervention of technological tools. The instruments used were observation, meetings and interviews, a qualitative approach intervened, making the interpretation process clear. Followed by agile practices, which helped manage workflows and making deliveries to the client in partial times, as results it has been possible to show that the information will be stored in a database at the time of requiring some management, the search will be more easy, it has advertising, the management of the company's services is shown through statistical tables together with the reports of the activities carried out. The main objective of the project was the creation and implementation of the progressive web application, since it fulfilled what was required, it was validated through tests by the end user, meeting the proposed expectations.